2003
DOI: 10.1029/2003gl017736
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of northeast Japan forearc and its implications for interplate seismic coupling

Abstract: [1] We determined, for the first time, a 3-D seismic structure of P and S wave velocity (Vp, Vs) in the forearc region of northeast (NE) Japan from the Pacific coast to the Japan Trench using a large number of high-quality arrival times from sub-oceanic earthquakes that are well located with sP depth phase data. Strong lateral heterogeneities in Vp and Vs are revealed. A majority (95%) of great interplate earthquakes are located outside the low-V zones while a few (5%) of them are located inside the low-V zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 17 publications
5
39
0
Order By: Relevance
“…However, the velocity images (Figures 2a -2d) obtained by inverting arrival time data with aftershocks show a wider distribution around the Miyagi-oki source zone, which may indicate the possibility that the pre-existing weak rupture zone within the slab might have been reinforced by the Miyagi-oki earthquakes. The slow anomalies in the mantle wedge right above the subducting slab (Figure 2) may show the serpentinization of the forearc mantle caused by the dehydration of the Pacific slab [Hyndman and Peacock, 2003;Mishra et al, 2003].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the velocity images (Figures 2a -2d) obtained by inverting arrival time data with aftershocks show a wider distribution around the Miyagi-oki source zone, which may indicate the possibility that the pre-existing weak rupture zone within the slab might have been reinforced by the Miyagi-oki earthquakes. The slow anomalies in the mantle wedge right above the subducting slab (Figure 2) may show the serpentinization of the forearc mantle caused by the dehydration of the Pacific slab [Hyndman and Peacock, 2003;Mishra et al, 2003].…”
Section: Resultsmentioning
confidence: 99%
“…The second group is of 690 sub-oceanic earthquakes that occurred during a period from October 1989 to March 2003. The hypocenter locations of 690 sub-oceanic earthquakes are well determined by using sP depth phases [Umino et al, 1995;Mishra et al, 2003]. The third group consists of 150 aftershocks whose hypocenters were located accurately by Hi-net.…”
Section: Methodsmentioning
confidence: 99%
“…Mishra et al, 2003;Yamamoto et al, 2006;Zhao et al, 2011) have shown that the P-wave velocities at the bottom of the forearc mantle wedge are low in segment B and high in segments A and C. Therefore, we infer that the Pwave velocity of the entire forearc mantle is lower in segment B than in the neighboring segments.…”
Section: P-wave Velocity Within the Forearc Mantle Wedgementioning
confidence: 90%
“…Tomographic velocity models derived from local earthquake data have shown that seismic velocities at the bottom of the forearc mantle wedge, i.e., just above the plate boundary, are low in the weakly coupled segment B and high in the neighboring segments A and C (e.g. Mishra et al, 2003;Yamamoto et al, 2006;Zhao et al, 2011). These studies suggested that the low velocity at the bottom of the forearc mantle wedge might be associated with forearc mantle hydration.…”
Section: Introductionmentioning
confidence: 92%
“…The measured earthquake records constitute only a small part of continuous record after a seismic rupture initiation that can influence the seismic triggered event analysis, involving a pre-fixed time interval of a continuous record of time-series data for pre and post event analysis. Conventional models for interpreting the physical state of the crust before and after earthquakes often fail to explain the associated fault dynamics and stress transfer mechanism involved in seismogenesis [6][7]. The major constraint in the development of scientific instrumentation for use in an earthquake early warning system (EEWS) is related to the uncertainty related to the ground truth location and inaccuracy arising from errors in location and focal depth.…”
Section: Introductionmentioning
confidence: 99%